Instilling Self-regulation in Children with Autism (Case Study in SLBN (State Special School) Kuala Tungkal) - Bangsawan, Indra; Ridwan, Ridwan; Utami, Supriyana; Hayati, Hayati; Huda, Huda; Annisa, Annisa; Mushlih, Ahmad (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2023)
The problem in this study is the need to instill self-regulation in early childhood to control children's minds in learning activities and emotions and instill behavior control in friends in their environment. If it can be instilled, then autistic children can concentrate on learning. The learning process so far is rarely done on children if they do not like the activity or the subject matter they are studying. This research aims to find out how to foster self-regulation in autistic children. This research is descriptive-qualitative, while the data collection methods used are observation, interviews, and documentation to find answers to the problems raised. The conclusion is instilling Self Regulation in autistic children by providing positive reinforcement in learning autistic children, stimulating responsive language skills, and practicing the expressive language in children, which can help them become individuals who are independent, responsible, and able to manage emotions and behavior. , and daily tasks effectively. This research has an update that focuses more on autistic children, namely developing self-regulation by providing guidance and appropriate behavior models to help children practice and strengthen their self-regulation skills.